Dynamic Effects of Foreign Direct Investment When Credit Markets are Imperfect - Thomas Gall; Marc Schiffbauer; Julia Kubny (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
This paper argues that foreign direct investment in economies with credit market imperfections may increase their vulnerability to capital flow shocks. Due to better access to financial markets foreign firms can use other wage contracts than domestic ones. This alters the domestic wage composition and the subsequent wealth distribution. When credit markets are imperfect, the wealth distribution typically determines an economy's growth potential in autarky; hence, high exposure to foreign direct investment may significantly impede the capability to recover from sudden withdrawals of foreign capital. This is substantiated by empirical evidence on durations of output recovery after systemic sudden stops.
Keywords: F43; F23; O16; 330; Credit market imperfections; foreign direct investment; growth; occupational choice; sudden stops